Effectiveness of Lesson Study-Based Professional Development on developing the teaching self-efficacy of mathematics teachers in the Sultanate of Oman - Al-Anbouri, Nasser Saed; Alghafri, Mohammed Saed (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to investigate the Effectiveness of Lesson Study-Based Professional Development on developing the teaching self-efficacy of mathematics teachers in the Sultanate of Oman. The study consists of (22) mathematics teachers, from two schools in South Batinah Governorate of Sultanate Oman. To answer the study questions, The teachers' self-efficacy scale were designed by the researchers. This scale was verified by several judges in the field, and the validity and reliabilities of these tools were calculated. After implementing the tools, the results showed a statistically significant difference between the means scores of mathematics teachers in pre and first post applications of the teachers' self-efficacy scale, in favor of first post-application, and there was a statistically significant difference between the means scores of mathematics teachers in the first post and second post applications of the teachers' self-efficacy scale, in favor second post-application. In the light of the above results, several recommendations were proposed, such as providing support and teaching materials to enable teachers to implement the lesson study approach in schools. In addition, the researcher suggested further investigating the effectiveness of the Lesson Study Approach at different variables related to teachers, and to what extent reflects on their students' learning of other topics in mathematics.
Keywords: Professional Development; Lesson Study; Teaching Self-Efficacy